Identification and functional analyses of CBS alleles in Spanish and Argentinian homocystinuric patients - Cozar, Mónica (2011)
Homocystinuria due to CBS deficiency is a rare autosomal recessive disorder characterized by elevated plasma levels of homocysteine (Hcy) and methionine (Met). Here we present the analysis of 22 unrelated patients of different geographical origins, mainly Spanish and Argentinian. Twenty-two different mutations were found, 10 of which were novel. Five new mutations were missense and five were deletions of different sizes, including a 794-bp deletion (c.532-37-736 + 438del794) detected by Southern blot analysis. To assess the pathogenicity of these mutations, seven were expressed heterologously in Escherichia coli and their enzyme activities were assayed in vitro, in the absence and presence of the CBS activators PLP and SAM. The presence of the mutant proteins was confirmed by Western blotting. Mutations p.M173del, p.I278S, p.D281N, and p.D321V showed null activity in all conditions tested, whereas mutations p.49L, p.P200L and p.A446S retained different degrees of activity and response to stimulation. Finally, a minigene strategy allowed us to demonstrate the pathogenicity of an 8-bp intronic deletion, which led to the skipping of exon 6. In general, frameshifting deletions correlated with a more severe phenotype, consistent with the concept that missense mutations may recover enzymatic activity under certain conditions.